2002
DOI: 10.1262/jrd.48.343
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Changes in Testicular Function and Inhibin Secretion of Golden Hamsters (<i>Mesocricetus auratus</i>)

Abstract: Abstract. We studied developmental reproduction of male golden hamsters (Mesocricetus auratus) by determining hormone secretion, observing morphological changes including distribution of immunoexpression of inhibin α subunit, 3β-hydroxysteroid dehydrogenase (HSD), and investigating sperm head count from birth to adulthood. Immunoexpression of inhibin α subunit was found in interstitial cells of not well organized testes of neonatal animals, and positive staining was also found in Sertoli cells in developing an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
1

Year Published

2003
2003
2003
2003

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 29 publications
(36 reference statements)
1
1
1
Order By: Relevance
“…FSH is a potent stimulator of inhibin production [1]. Plasma concentrations of FSH in the premature hamster are relatively high, and the levels are almost equal to those of sexually mature animals [3,21]. In contrast to premature animals, FSH levels found in sexually inactive animals, induced by exposure to short photoperiod in the present study, were clearly lower than those in sexually active mature males.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…FSH is a potent stimulator of inhibin production [1]. Plasma concentrations of FSH in the premature hamster are relatively high, and the levels are almost equal to those of sexually mature animals [3,21]. In contrast to premature animals, FSH levels found in sexually inactive animals, induced by exposure to short photoperiod in the present study, were clearly lower than those in sexually active mature males.…”
Section: Discussioncontrasting
confidence: 49%
“…We used the method of immunoneutralization against endogenous inhibin and this is one of good model fo r demonstrating that inhibin ha s a physiological role in the regulatio n of FSH secretion. We also demonstrated the changing pattern of plasma concentrations of FSH and inhibin during development in male hamsters [3]. We found a reciprocal changing pattern between plasma concentrations of FSH and inhibin, and we concluded that inhibin in developing male golden hamsters controlled FSH secretion.…”
supporting
confidence: 52%
See 1 more Smart Citation